Peritoneal mesothelioma. Issue 780 (October 1990) - Anderson, J. H.; Stewart, C. J.; Hansell, D. T.; Anderson, J. R.
Abstract : We report two patients who presented with small bowel obstruction secondary to peritoneal mesothelioma. The difficulties in establishing this diagnosis at an early stage are illustrated. Recent advances in the management of peritoneal mesothelioma are reviewed.